Microbiological properties of root zone of coconut grown in different soil series in Sri Lanka - K.S.K.S. Fernando; N.A. Tennakoon; S. Widanapathirana (International Coconut Community Journal, 2004)
In Sri Lanka, coconut is cultivated under diverse soil conditions of varying fertility status available in different agro-climatic zones. Although chemical and physical characteristics in some of these soils are known, their biological properties are yet to be studied. Hence the aim of this study was to determine the microbiological parameters in root zone of coconut grown in different soil series. For this study, 20 different soil series in coconut growing area were analyzed for number of total bacterial and fungal colonies, identification of bacteria and fungi, biomass C and N; CO2 evolution and nitrogen mineralization. The microbiological parameters varied with the soil series. The bacterial population densities were significantly (p=0.001) high in Ambakelle, Kalpitiya, Rathupasa and Madampe soil series while the fungal colonies were significantly (p=0.001) high in Thambarawa, Pallama, Wilatawa and Ambakelle soil series.